2022
DOI: 10.1097/gox.0000000000004111
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma Gangrenosum after Breast Cancer Resection: A Less-invasive and Early Treatment Using the Skin around Ulcers

Abstract: Summary: Surgical invasion is a risk factor of pyoderma gangrenosum (PG). A total of 25% of postoperative PG cases were reported to occur after breast surgeries, including bilateral breast reduction and breast reconstruction following cancer resection. Immunosuppressive therapy and less-invasive wound therapy are necessary; however, the complete healing of ulcers takes 5.1 months on average. We herein report a case of skin grafting under a surgical concept of less-invasive and short-term treatment. An 82-year-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…As previously stated, subatmospheric pressure therapy increases tissue perfusion and granulation tissue formation while decreasing the bacterial load and interstitial edema 8. Case studies suggest that NPWT with systemic corticosteroids may be effective for PG 13,14. Additionally, Pichler and colleagues15 reported improvement of PG in 13 of 15 patients who received NPWT with split-thickness skin grafts, with complete resolution in 9 patients.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…As previously stated, subatmospheric pressure therapy increases tissue perfusion and granulation tissue formation while decreasing the bacterial load and interstitial edema 8. Case studies suggest that NPWT with systemic corticosteroids may be effective for PG 13,14. Additionally, Pichler and colleagues15 reported improvement of PG in 13 of 15 patients who received NPWT with split-thickness skin grafts, with complete resolution in 9 patients.…”
Section: Discussionmentioning
confidence: 91%
“…8 Case studies suggest that NPWT with systemic corticosteroids may be effective for PG. 13,14 Additionally, Pichler and colleagues 15 reported improvement of PG in 13 of 15 patients who received NPWT with split-thickness skin grafts, with complete resolution in 9 patients. Another case study reported healing of refractory PG with NPWT and intravenous immunoglobulin (IVIg).…”
Section: Discussionmentioning
confidence: 99%